TRIBO-FATIGUE Wear-Fatigue Damage and its Prediction - Sosnovskiy, Leonid A. (Foundations of Engineering Mechanics,, 2005)
Fatigue and wear are the most damaging phenomena affecting machines since they result in some 90% of breakdowns. This tutorial book systematically develops a unified overview, named tribo-fatigue, which aims to address the complex wear-fatigue damages. Tribo-fatigue synthesizes aspects of three disciplines: mechanical fatigue, tribology, and reliability of mechanical systems. Tribo-fatigue opens new perspectives for increasing the durability of machines according to the most important criteria of their serviceability. Detailed damage measurement and wear-fatigue tests that enable engineers to design more durable and reliable systems are developed. The book is intended for advanced students, researchers and engineers.